2008
DOI: 10.1007/s00167-008-0631-x
|View full text |Cite
|
Sign up to set email alerts
|

Failure load of patellar tendon grafts at the femoral side: 10- versus 20-mm-bone blocks

Abstract: The aim of the study was to investigate whether use of short bone blocks is safe in anterior cruciate ligament (ACL) reconstruction. Our hypothesis was that the smaller 10-mm-length bone blocks will fail at lower loads than 20-mm-bone blocks. Ten paired human cadaver knees were randomly assigned to the 10-or 20-mm group (group 1 and 2) and underwent bone-patellar tendon-bone femoral fixation with interference screw. Tensile tests were performed using a tensile testing machine (Instron). Stiffness, failure load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…Our human cadaveric study shows an average pullout strength of 434 AE 85N for all bone plug lengths between 20and 10-mm, somewhat more than the Meuffel et al's human cadaver femoral construct (410 AE 171N), which utilized 20and 10-mm plug length only. 31 The average pullout strength of our study is less than a study by Posner who utilized porcine bone. They found a pullout force of 658 AE 92N for 15 mm plugs and 540 AE 203N for 20 mm plugs compared with our 437 AE 74N for15 mm P þ T plugs and 457 AE 66N for 20 mm P þ T plugs.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Our human cadaveric study shows an average pullout strength of 434 AE 85N for all bone plug lengths between 20and 10-mm, somewhat more than the Meuffel et al's human cadaver femoral construct (410 AE 171N), which utilized 20and 10-mm plug length only. 31 The average pullout strength of our study is less than a study by Posner who utilized porcine bone. They found a pullout force of 658 AE 92N for 15 mm plugs and 540 AE 203N for 20 mm plugs compared with our 437 AE 74N for15 mm P þ T plugs and 457 AE 66N for 20 mm P þ T plugs.…”
Section: Discussioncontrasting
confidence: 53%
“…As far as we know, patella versus tibia plug subgroup cross-analysis has not been reported in the literature (►Table 2). 22,23,25,[27][28][29][30][31] The results disprove our hypothesis, however, based on the shorter 10 mm tibia bone plugs achieving rigid fixation even though bone density of the tibia plug is generally softer than the patella side. Our hypothesis was based on the idea that tibia porosity would weaken plug stability, not render it resistant to tension loading, the latter of which appears to have been possible in our experiment.…”
Section: Discussionmentioning
confidence: 47%
“…In reconstruction using Achilles allograft, bone‐to‐bone fixation with interference screw has been conventionally used in femoral tunnel. Many studies have been reported that failure load in bone‐to‐bone fixation with interference screw is positive and that bone‐to‐bone fixation is more stable and heals faster than soft tissue‐to‐bone fixation [8, 13, 19, 22]. However, Achilles allograft sometimes cannot be firmly fixed due to cracks in bone plug of allograft while preparing, pulling a graft into the tunnel, fixating, or even pretensioning after femoral fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 study, to date, has looked at the length of bone block. Meuffels et al 9 performed a biomechanical test of 10- versus 20-mm bone block in ultimate load-to-failure testing and showed no statistical difference between the 2 lengths. However, this study was not performed with cyclic loading, which more accurately replicates the in vivo rehabilitation environment of the early post-ACL reconstructed knee.…”
mentioning
confidence: 99%